Awareness of local communities about the value of their city’s cultural heritage and the need to protect it on the example of selected historic towns in the Małopolska region (Poland) - Kuśnierz-Krupa Dominika; Sandu Ion; Tišliar Pavol; Bednarz Łukasz; Dmytrenko Andrii; Ivashko Oleksandr; Cechini Klaudia (Technical Transactions)
This article focuses on the problem of local communities’ awareness of heritage values in terms of urbanism, architecture, and construction and the traditions of place within a historic town. To study this problem, the authors conducted qualitative and quantitative research using the questionnaire method. They were carried out in the area of two selected small historic towns located in southern Poland in the Małopolska region: Muszyna and Piwniczna-Zdrój. Their aim was to determine the level of awareness of the cultural heritage values of both towns among their inhabitants. The results of the research are expected to identify areas of real educational needs in terms of the knowledge and a sense of value of local monuments. The authors believe that social participation and involvement of local communities is essential in the process of protecting and caring for monuments of indigenous cultural heritage.